2017
DOI: 10.1002/nau.23328
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder symptoms after midurethral sling surgery in women: Risk factors and management

Abstract: OAB symptoms are frequently reported after sling surgery. Women with mixed incontinence and older women are at risk of developing post-operative OAB symptoms. We have proposed an algorithm for the treatment of these symptoms which can be useful in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 39 publications
5
44
0
3
Order By: Relevance
“…In the present study, nine patients developed de novo urgency after surgery. Recently Marcelissen and van Kerrebroeck reviewed the literature, including 10 papers with >2800 patients, and found several risk factors including obesity, older age, lower bladder capacity, previous urgency or history of UI surgery. Older age and previous urgency appear to be the more consistent risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, nine patients developed de novo urgency after surgery. Recently Marcelissen and van Kerrebroeck reviewed the literature, including 10 papers with >2800 patients, and found several risk factors including obesity, older age, lower bladder capacity, previous urgency or history of UI surgery. Older age and previous urgency appear to be the more consistent risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Marcelissen et al (3) conducted a literature review including 10 studies and 3132 patients. The study concluded that patients with MUI were more likely to develop OAB symptoms after surgery for SUI as mentioned in our study (only 9 patients developed de novo OAB symptoms).…”
Section: Discussionmentioning
confidence: 99%
“…If pelvic floor training which contributes to the support of the female urethra fails, surgical treatment for SUI is considered (3). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed symptoms represent the majority and most challenging subpopulation among those with incontinence (3). Moreover, even the sling implant can potentially lead to the worsening of storage symptoms in patients with pre-operative mixed urinary incontinence.…”
Section: Article Infomentioning
confidence: 99%